Impact of parental care on depression and academic performance of adolescent girls from selected schools in a city in South India - Gopakumar, Soumya; Johns, Sandra (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence is a transitional period where the relationship between them and their parents are vital. Mental health status of girls staying in poor homes without parental care may influence their academic performance and since need special attention. So a study was undertaken to assess the depression status of adolescent girl students (13-15yaers) in selected schools using Kutcher Adolescent Depression Assessment Scale (KADS) given by Kutcher and to compare the depression scores, academic and other socio-demographic factors of adolescent girls with and without parental care. Methods: Cross sectional study involving 130 girl students from selected schools of which 40 students were from poor homes. Chi -square test and Mann Whitney U test was used as test of significance for qualitative and quantitative variables respectively. Binary logistic regression was also used. Results: Analysis of KADS score indicated that both type of students with and without parental care had similar cumulative scores varying from 1- 19. Among the study subjects 10 (7.7% with 95 % confidence interval 3.12% - 12.28%) had scores above 15. Academic performances and participation in arts and sports were significantly different between students staying with parents than those from poor homes. Conclusions: Percentage of students from poor homes with collective KAD scores above 15 is almost double the percentage of students with parental care. Parental support is positively related to better academic and extracurricular activities of students.